Free for all - Horvath, Patrick (Filmmaker) (Oni Press, 2026)
"A biting, visually arresting critique of greed and excess that will resonate with readers drawn to speculative fiction, political allegory, or horror-tinged social commentary." --Library Journal From Eisner Award-nominated writer/artist Patrick Horvath (Beneath the Trees Where Nobody Sees) comes a brutal new vision of capitalism by combat . . . In the future, the World Finance League exists to benefit all, randomly choosing those from among the billionaires and trillionaires of the world and presenting them with a choice: Either donate half of their assets to the common good--or defend them in ritual combat. Reigning champion and real estate magnate Ted Brooks has 22 victories under his belt--defending the wealth he schemed and stabbed to get--when he is forced to face his ex-wife, Luella Dominguez, in a fight to the death. Luella has been training, waiting for this moment. But will she have what it takes to defeat the man who would do anything--absolutely anything--to keep his fortune? It's every shareholder for themselves when death and bankruptcy collide!